Nano‐Porous Electro‐Catalyst with Textured Surface Active Pd‐Pt Islands for Efficient Methanol Tolerant Oxygen Reduction Reaction. Issue 25 (1st September 2017) - Anandha Ganesh, P.; Jeyakumar, D.
Abstract: Herein, we report a simple and elegant aqueous synthesis of Pd100‐x Ptx (x=5, 10, 15 and 20) nano‐porous structures (NPoS) derived from Pd100‐x Mn2x (x=5, 10, 15 and 20) nano‐alloys. Pd100‐x Ptx /C NPoS exhibit enhanced oxygen reduction reaction (ORR) activity along with higher retention of figure of merit in the presence of methanol compared to HiSPEC Pt/C catalyst. The ORR mass and specific activity values of Pd100‐x Ptx /C NPoS are high and exceed the U.S. department of energy (DOE) 2017–2020 targets. The enhanced methanol tolerance and ORR activity of Pd100‐x Ptx /C NPoS is attributed to their unique surface active Pd−Pt islands on nano‐porous Pd. Direct methanol fuel cell performance studies employed using Pd85 Pt15 /C NPoS as cathode material (0.4 mgPt /cm 2 ) and HiSPEC PtRu/C NPs as anode material (0.2 mgPt /cm 2 ) shows improved direct methanol fuel cell (DMFC) single cell activity at low Pt loading and the results are presented. Abstract : Textured unique surface for methanol tolerance ORR: Pd85 Pt15 /C nano‐porous electro‐catalyst exhibits efficient methanol resistant oxygen reduction activity attributed to the presence of surface textured unique Pd−Pt islands.